2014
DOI: 10.1523/jneurosci.0433-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Knock-In of Human BACE1 Cleaves Murine APP and Reiterates Alzheimer-like Phenotypes

Abstract: Key neuropathological hallmarks of Alzheimer's disease (AD) are elevated levels of amyloid ␤-peptide (A␤) species generated via amyloid precursor protein (APP) endoproteolysis and cleavage by the rate-limiting ␤-site enzyme 1 (BACE1). Because rodents do not develop amyloid pathologies, we here investigated whether AD-like endophenotypes can be created in mice by expression of human bace1. To avoid pitfalls of existing models, we introduced hbace1 via knock-in under the control of the CaMKII ␣ promoter into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 75 publications
1
62
0
Order By: Relevance
“…In support of this, soluble Ab accumulation has also been proposed to play the key role human AD pathogenesis (Gouras et al, 2000;Lesné et al, 2006Lesné et al, , 2013. Previous data from our PLB lines confirmed that soluble Ab and potentially tau fragments are key players in AD neurodegeneration (see also Pluci nska et al, 2014) and, therefore, suggest that soluble species may play a vital role in sleep-wakefulness disturbances.…”
Section: Histopathologysupporting
confidence: 78%
See 2 more Smart Citations
“…In support of this, soluble Ab accumulation has also been proposed to play the key role human AD pathogenesis (Gouras et al, 2000;Lesné et al, 2006Lesné et al, , 2013. Previous data from our PLB lines confirmed that soluble Ab and potentially tau fragments are key players in AD neurodegeneration (see also Pluci nska et al, 2014) and, therefore, suggest that soluble species may play a vital role in sleep-wakefulness disturbances.…”
Section: Histopathologysupporting
confidence: 78%
“…For data acquired over time, a repeated-measures ANOVA was applied. Habituation behavior was further probed using a 1-phase decay fit and statistically compared using the extra sum of squares F test based on plateau and K values as parameters (for details, see Pluci nska et al, 2014).…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a report that overexpression of wild type (WT) human tau in a tau knockout background can lead to NFTs, implying that mouse tau might be inhibitory to the process (Andorfer et al, 2003). In addition, a recent study demonstrated that a knockin of human BACE1 enhanced murine Aβ production and was sufficient to cause cognitive deficits, suggesting that regulators of APP processing are also different in mice (Plucinska et al, 2014). Overall this suggests that there are species-specific differences in APP and Tau and how the brain responds to mutant versions of FAD genes.…”
Section: Article In Pressmentioning
confidence: 99%
“…20 Moreover, several neuropsychiatric symptoms, such as abnormalities in emotionality/activity, social interactions and sensomotor abilities are commonly detected in AD patients (Lyketsos et al, 2011). Deficits in working memory and social interactions that have been described for DISC1 mutant mice (Ayhan et al, 2011;Koike et al, 2006;Pletnikov et al, 2008) are also observed in BACE1 knock-in transgenic mice (Plucinska et al, 2014).…”
Section: Discussionmentioning
confidence: 93%